The Kommerell test, and the guidelines of SEP 1390:1996 - Jakub Kozłowski (Przegląd Spawalnictwa, 2018)
The article presents a comparison of weldability assess- ment samples according to the Kommerell sample and SEP 1390 guidelines. The aim of the topic was to compare sample preparation, test run and analysis of Kommerell test results and SEP 1390 sample to assess the weldability of construction materials.